PEMANFAATAN EKSTRAK MINYAK DAUN JERUK PURUT PADA EDIBLE FILM BERBASIS GELATIN KULIT CEKER AYAM YANG DIAPLIKASIKAN PADA SOSIS SAPI: UTILIZATION OF CHICKEN SHANK AS A MATERIAL OF GELATIN-BASED EDIBLE FILM SUPPLEMENTED BY KAFFIR LIME OIL EXTRACT ON BEEF SAUSAGE COATING - Rohman, Fatkur; Abdurrahman, Zakaria Husein; Purwadi, Purwadi (Universitas Boyolali, 2024)
Sausage is a product made from minced meat and then mashed and seasoned, put in artificial packaging, with or without cooking.) due to both oxidative and microbiological damage. Chicken feet are a by-product of chicken slaughterhouses (RPA) whose use is limited because they contain a lot of bones and a little meat, but have a high skin content. The chicken leg consists of several parts such as bone, skin, muscle and collagen. Chicken claw contains collagen of 22.94%. In this study there were 7 stages, namely making gelatin, making kaffir lime oil, making samples, dividing samples, organoleptic tests, hedonic tests, and data analysis. The results of this test indicate that beef sausages coated with edible film with the addition of kaffir lime leaf extract are declared fit for consumption. Because this value is still below the total microbial standard according to SNI (1x106 CFU/g), so beef sausage is still suitable for consumption.